(untitled) (Revista de Biología Marina y Oceanografía, 2023)
The coastal waters of Ecuador have emerged as a favorable environment for the growth and development of several species of edible macroalgae or seaweeds. In this study, fatty acid profiles, total soluble polyphenol content, and antioxidant capacity of seven species of macroalgae (four red algae, two brown algae and one green algae) collected from Salinas Bay, Santa Elena Province, Ecuador, were evaluated. Saturated fatty acids C14:0, C15:0, C16:0 and C18:0 were found in almost all organisms, from which palmitic acid showed the highest proportion (10.7-37.1%). Green and brown seaweeds exhibited a major content of unsaturated fatty acids. Monounsaturated fatty acid composition was represented by several isomers of C16:1 and C18:1, mainly palmitoleic (3.0-6.6%) and oleic (0.8-11.1%) acids. Polyunsaturated fatty acid composition ranged from 5.47 to 26.61%, with ratios of total n-6/n-3 acids lower than 3.3. Linoleic (C18:2, n-6, 1.16-7.73%) and eicosapentaenoic (C22:5, EPA, n-3, 1.44-5.92%) acids were found in the majority of the seaweeds. The total polyphenol content of the seaweeds was determined by the Folin-Ciocalteu method (765 nm), and ranged from 147.28 to 1,062.20 mg equivalents of gallic acid (GAE) per 100 g of dry seaweed. The antioxidant capacity was determined by the Trolox equivalent antioxidant capacity (517 nm). Only Acanthophora spicifera, Spatoglossum schroederi, and Ulva lactuca showed good radical-scavenging (14.18-3,379.47 mg Trolox equivalents (TE) per 100 g of dry seaweed). The results confirm the potential use of macroalgae in the study area as an important source of nutritional compounds, especially brown and green algae, which could be a recommended food supplement even in the treatment of some diseases.